Sensitisation of the IFNγ-Stat1-signalling-pathway in rheumatoid arthritis monocytes. (22nd February 2011) - Karonitsch, Thomas; Dalwigk, Karolina; Steiner, Carl W; Blüml, Stefan; Steiner, Günter; Kiener, Hans; Smolen, Josef S; Aringer, Martin
Abstract : Background: Both, type I interferons (IFNα, IFNβ) and the type II IFN IFNγ signal via phosphorylating Stat1. Immunohistochemistry and gene expression signatures of synovial tissues suggest an activated IFN-Stat1-signalling-pathway in rheumatoid arthritis (RA). This study was performed to determine the activity of the IFN-Stat1-signalling-pathway in RA peripheral blood monocytes. Methods: Flourocytometry or qPCR was used to measure the expression of Stat1, phospho-Stat1 (pStat1) and IFN-inducible genes, such as IP-10 and OAS in RA and healthy (HC) peripheral blood monocytes. To examine the significance of Stat1 and of the IFNγ-inducible chemokine MIG (monokine induced by IFNγ) were measured using fluorocytometry. Results: Levels of Stat1 and pStat1 protein expression were significantly increased in RA monocytes when compared to HC (mfi 14.7±8.1 vs 8.0±3.9, p=0.0002; mfi 5.1±1.3 vs 3.2±0.7, p<0.0001, respectively). Stat1 mfi in RA monocytes correlated with RA disease activity such as DAS28 (Disease Activity Score; r=0.47, p<0.008) or CDAI (Clinical Disease Activity Index; r=0.51, p<0.003). Further, Stat1 mRNA expression in RA monocytes correlated with the expression of other IFN target genes, such as IP-10 or OAS. RA monocytes demonstrated a considerably higher increase in pStat1 and MIG levels upon IFNγ stimulation when compared to monocytes from HC (pStat1: +2.8±1.8 vs +1.5±1.1, p<0.03; MIG: +565±351 vs +303±253, p<0.05), indicating that RA monocytes are more sensitive to IFNγ stimulation. Conclusions: Consistent with a systemic proinflammatory activity of RA monocytes, these studies suggest activation of the IFNγ-Stat1-signalling pathway in RA.